Imitation in Chinese Preschool Children: Influence of Prior Self-Experience and Pedagogical Cues on the Imitation of Novel Acts in a Non-Western Culture - Wang, Zhidan; Meltzoff, Andrew N. (Frontiers in Psychology, 2020)
Both prior experience and pedagogical cues modulate Western children’s imitation. However, these factors have not been systematically explored together within a single study. This paper explored how these factors individually and together influence imitation using 4-year-old children born and reared in mainland China (N = 210)—a country that contains almost one-fifth of the world’s population, and in which childhood imitation is under-studied using experimental methodology. The behavior of children in this culture is of special interest to theory because traditional East Asian culture places high value on conformity and fitting in with the group. Thus, high-fidelity imitation is emphasized in the local culture. This value, practice, or norm may be recognized by children at a young age and influence their imitative performance. In this study, we crossed prior self-experience and pedagogical cues, yielding 4 demonstration groups in addition to a control group. This design allowed us to investigate the degree to which Chinese preschoolers’ imitation was modulated by the two experimental factors. High-fidelity imitation was significantly modulated by prior self-experience but not by pedagogical cues, as measured by the number of novel acts imitated and also the serial order of these acts. This study (i) expands our understanding of factors that modulate imitation of novel behaviors in preschoolers and (ii) contributes to efforts to broaden research beyond Western societies to enrich our theories, particularly regarding social learning and imitation. Imitation is a key mechanism in the acquisition of culturally appropriate behaviors, mannerisms, and norms but who, what, and when children imitate is malleable. This study points to both cross-cultural invariants and variations to provide a fuller picture of the scope and functions of childhood imitation.